ANALISIS WACANA TEKSTUAL PADA LIRIK LANGGAM IMPENKU KARYA KI NARTOSABDO - Aziza, Lutfi Nur (PT. Intelek Cendikiawan Nusantara, 2025)
This article aims to analyze the textual discourse contained in the lyrics of the Javanese song Langgam Impenku by Ki Nartosabdo. The approach used in this study is qualitative and the descriptive qualitative method of textual discourse that focuses on the meaning produced from the song's lyrics. The analysis was carried out by identifying the language elements that form the message in the lyrics of the langgam. The results of the study lead to the lyrics of Langgam Impenku which not only reflect the personal feelings of the creator, but also contain Javanese cultural values. This study is expected to contribute to the development of discourse studies in Indonesian traditional music, especially in the context of Javanese langgam lyrics.